Mastery of endoscopic and laparoscopic surgery - Leonard, Michael; Soper, Nathaniel J.; Swanstro?? e??m, Lee L. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins Health, 2014)
If there is a theme to this edition, it probably lies in the fact that most of the laparoscopic operations described are well-matured and backed with many years of outcomes data to support their gold standard status. This is an increasingly important component of any surgical approach in this era of cost containment and effectiveness measurements. We hope that the evidence listed in this edition will provide a ready reference for surgeons who need to defend their choice of a minimally invasive approach for their patients. A second theme to note is the continued emphasis on the utility and importance of flexible endoscopy as a surgical tool. As more and more operations, even laparoscopic ones, become doable by the flexible endoscope, it is increasingly apparent that the surgeon who relinquishes their right to perform endoscopy will face an increasingly narrow spectrum of practice. Mastery of Laparoscopic and Endoscopic Surgery has always reflected this philosophy, in this edition more than ever, and we are happy to see that the current political efforts by the American Board of Surgery and other leadership groups in surgery validate this emphasis--Provided by publisher.
Includes bibliographical references and index.
Keywords: Endoscopy; Laparoscopy